The relationship between the myodural bridge, vertebrodural structures, and idiopathic cerebrospinal fluid leaks in whiplash injuries. (August 2022) - Chien, Krizia; Keehn, William; Scali, Frank
Abstract: Cerebrospinal fluid leaks have been noted as a radiological finding in some post-whiplash patients. However, the mechanism for these leaks has not yet been described. Anatomical studies have recently reported deep suboccipital muscles attaching to the cervical dura mater via myodural bridging structures. Excessive tension across these myovertebral structures may rupture the dura mater at their attachment sites, particularly in patients with underlying connective tissue disorders. Whiplash events may provide the necessary tension across the myodural bridging structures to rupture the dura mater allowing extravasation of cerebrospinal fluid into the retrospinal region at the atlantoaxial interspace. As such, cerebrospinal fluid extravasation following a whiplash event that has been previously described as idiopathic or spontaneous may result from excessive myodural and vertebrodural tension leading to dural tears following whiplash events.